The Effect of Well Child Visit Location on Preventative Dental Visit - Tamanna Tiwari; Jennie Marinucci; Eric P. Tranby; Julie Frantsve-Hawley (MDPI AG, 2021)
Recent emphasis has been placed on the integration of dental and medical primary care in an effort to promote recommendations from both American Academy of Pediatrics (AAP) and American Academy of Pediatric Dentistry (AAPD) that highlight the importance of preventing, intervening, and managing oral disease in childhood. The study aims to provide a population level insight into the role of location of service of medical well-child visit (WCV) and its association to preventative dental visit (PDV) for children between the ages of 0-20 years. Administrative claims data for 3.17 million Medicaid-enrolled children aged 0 to 20 years of age in 13 states in 2016 and 2017 were identified from the IBM Watson MarketScan Medicaid Database. Descriptive and survival analysis reveals most Medicaid enrolled children receive their WCV at an office and hospital, as compared to federally qualified health center, or rural or public health clinic. Further, this study demonstrates increased utilization of dental preventive services for children who receive a WCV. Hispanic children, female children, and children 5-9 years of age had a higher rate of PDV after a WCV at all three locations. This study contributes to the understanding of medical-dental integration among Medicaid-enrolled children and offers insight into the promotion of oral health prevention within medical primary care.